Cat swarm optimization for solving the open shop scheduling problem - Abdelhamid Bouzidi; Mohammed Essaid Riffi; Mohammed Barkatou (Journal of Industrial Engineering International, 2019)
This paper aims to prove the efficiency of an adapted computationally intelligence-based behavior of cats called the cat swarm optimization algorithm, that solves the open shop scheduling problem, classified as NP-hard which its importance appears in several industrial and manufacturing applications. The cat swarm optimization algorithm was applied to solve some benchmark instances from the literature. The computational results, and the comparison of the relative percentage deviation of the proposed metaheuristic with other's existing in the literature, show that the cat swarm optimization algorithm yields good results in reasonable execution time.
Keywords: 650; Scheduling problem; Swarm optimization; Behavior of cats; Computationally intelligence; Discrete